Analisis Penerapan Sanksi Hukum terhadap Pelaku Pelanggaran Pemanfaatan Ruang Laut - Prasetyo, Dwi Aji; Miharja, Marjan (Neolectura, 2026)
The growing intensity of human activities in marine areas increases the risk of conflicts and violations of marine spatial planning, making strong regulation and effective law enforcement essential for sustainable management. This study examines the legal framework governing violations of marine space utilization in Indonesia and explores efforts to strengthen legal norms and the effectiveness of criminal sanctions. Using a normative juridical method, the research analyzes relevant laws and regulations. The findings indicate that Indonesia has established a comprehensive system of administrative and criminal sanctions for marine space utilization violations, as regulated under the Job Creation Law and its implementing regulations. Parties utilizing marine space without a Marine Space Utilization Suitability Permit (KKPRL) may face administrative sanctions such as warnings, suspension of activities, permit revocation, fines, and criminal penalties if their actions result in changes to marine spatial functions. However, this study identifies a normative gap, particularly the absence of clear technical criteria for determining changes in marine space functions. This gap creates legal uncertainty and underscores the need for more detailed technical guidelines to ensure legal certainty, fairness, and sustainability in marine spatial management.